2022
DOI: 10.3390/su14063135
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of ETICS in the Context of Energy and Social Changes (Case Study)

Abstract: The paper focuses on the quality of external composite ETICS (External Technical Insulation Composite System) façade systems from a long-term perspective in the context of energy and social changes and subsequent paths of housing construction, including reconstructions and renovations of prefabricated housing developments. These changes follow mainly from the EU energy concept and strategy in relation to housing and have an impact potential well beyond 2030. The aim of the paper is to show, based on field rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…More than 50 years of the application of ETICS have shown that it is a good solution in different climatic conditions and the factors that can affect the deterioration of the functional thermal insulation properties are relatively well mapped and described from both a theoretical and a practical point of view. However, there are failures in ETICS that we have not encountered before, such as the issue of deterioration of facades with ETICS by biotic agents [2,3]. Increasingly stringent legislative energy measures defined by the EU and the required fulfilment of thermal and energy criteria [4][5][6][7][8][9] leads to an increasing thickness of thermal insulation over time.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 years of the application of ETICS have shown that it is a good solution in different climatic conditions and the factors that can affect the deterioration of the functional thermal insulation properties are relatively well mapped and described from both a theoretical and a practical point of view. However, there are failures in ETICS that we have not encountered before, such as the issue of deterioration of facades with ETICS by biotic agents [2,3]. Increasingly stringent legislative energy measures defined by the EU and the required fulfilment of thermal and energy criteria [4][5][6][7][8][9] leads to an increasing thickness of thermal insulation over time.…”
Section: Introductionmentioning
confidence: 99%